2001
DOI: 10.1007/s002590100542
|View full text |Cite
|
Sign up to set email alerts
|

Radiation exposure and radiation protection of the physician in iodine-131 Lipiodol therapy of liver tumours

Abstract: Intra-arterial iodine-131 labelled Lipiodol therapy for liver cancer has been investigated for safety and efficacy over a number of years, but data on radiation exposure of personnel have remained unavailable to date. The aim of this study was to assess the radiation exposure of the physician during intra-arterial 131I-Lipiodol therapy for liver malignancies and to develop appropriate radiation protection measures and equipment. During 20 intra-arterial administrations of 131I-Lipiodol (1110-1924 MBq), radiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…In our study, the WBD values for the radiopharmacist (syringe filling) and radiologist (injection and catheter retrieval) were lower. This can be partly explained because syringe filling was performed behind a large bench-mounted lead shield (thickness, 60 mm) using a 10 mm syringe shield sealed with a tungsten cap and because we used a mechanical device for femoral haemostasis instead of manual compression as seen in the studies by Risse et al [5] and Garin et al [4].…”
Section: I-labelled Lipiodol Therapymentioning
confidence: 97%
See 4 more Smart Citations
“…In our study, the WBD values for the radiopharmacist (syringe filling) and radiologist (injection and catheter retrieval) were lower. This can be partly explained because syringe filling was performed behind a large bench-mounted lead shield (thickness, 60 mm) using a 10 mm syringe shield sealed with a tungsten cap and because we used a mechanical device for femoral haemostasis instead of manual compression as seen in the studies by Risse et al [5] and Garin et al [4].…”
Section: I-labelled Lipiodol Therapymentioning
confidence: 97%
“…We also report a safer way for syringe filling using tubes allowing a five-fold decrease of hand exposure and a decrease of annual finger dose from 20.6 mSv to 8.5 mSv. Risse et al [5] tested different methods for the preparation and administration of 131 Ilabelled Lipiodol by the nuclear medicine specialists and reported alarming results since the calculated dose at the level of the fingers varied between 5 mSv and 19.5 mSv per injection (1813( -1924. In this work, Risse et al, demonstrated the efficiency of their self-developed shielded container allowing finger dose reduction down to 3 mSv per injection.…”
Section: I-labelled Lipiodol Therapymentioning
confidence: 98%
See 3 more Smart Citations